158k views
1 vote
PLEASE HELP URGENT‼️‼️

Tonia was simplifying the expression: (3x)2 . x4. She wrote 3x8 as the
simplest form.
——————————————
Part A) Simplify the problem correctly.
——————————————
Part B) Describe the error(s) that Tonya made.

PLEASE HELP URGENT‼️‼️ Tonia was simplifying the expression: (3x)2 . x4. She wrote-example-1
User JimmyCYJ
by
5.6k points

1 Answer

0 votes

Part A

(3x)^2*x^4

(3x)*(3x)*x^4 .... expand out (3x)^2

(3*3)*(x*x*x^4)

9x^6

Answer: 9x^6

============================================

Part B

It appears that Tonya forgot to square the 3 term and had this as her steps

(3x)^2*x^4

3x^2*x^4

3x^(2*4)

3x^8

Which is incorrect as the answer in part A indicates.

Not only is the '3' part wrong, but also the exponent of 8. Instead of multiplying the exponents, she should have added them.

The rule is a^b*a^c = a^(b+c). In this case, a = x, b = 2 and c = 4.

So x^2*x^4 = x^(2+4) = x^6

User Valerie R
by
5.5k points